(untitled) (The Voz a Vos Bulletin, 2025)
Performing arts, as a pedagogical tool, hold transformative potential to make visible and reframe school coexistence dynamics. In contexts marked by intragender violence, such as the one observed at the Ciudadela Sucre Educational Institution – Sede B in Soacha, these artistic expressions can serve as a means to channel emotions, build collective narratives, and foster supportive bonds among female students. The presented research acknowledges the need to address bullying among girls through an approach that integrates sorority, understood as an ethical and political commitment to empathy, active listening, and mutual care. Through mixed methodologies, the study identifies Boletín Voz a vos 19 – enero a junio de 2025 26 how art can create safe spaces for dialogue and reflection, promoting key socioemotional skills for peaceful coexistence. In this sense, performing arts not only allow for the representation of conflicts but also their transformation, by nurturing the ability to see oneself in others. This experience invites us to view the school as a stage where, beyond learning academic content, students learn to coexist, to be with others, and especially to be with other women through respect, equity, and female solidarity.